Neurodevelopmental screening accessibility : translating the ‘Autism – Tics, ADHD & Other Comorbidities’ [A-TAC] inventory into isiXhosa and Afrikaans. - Nel, Jacques (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.